Like magic - Vickers, Elaine (Harper, an imprint of HarperCollins Publishers, 2016)
For three ten-year-old girls, their once simple worlds are starting to feel too big. Painfully shy Grace dreads starting fifth grade now that her best friend has moved away. Jada hopes she'll stop feeling so alone if she finds the mother who left years ago. And Malia fears the arrival of her new baby sister will forever change the family she loves. When the girls each find a mysterious treasure box in their library and begin to fill the box with their own precious things, they start to feel less alone. But it's up to Grace, Jada, and Malia to take the treasures and turn them into something more: true friendship.